Over-lexicalization and Under-lexicalization of Physical Violence Expression in Laut Bercerita and Its Translation by Leila S. Chudori - Amalia, Friska; Munandar, Aris (Langkawi: Journal of The Association for Arabic and English, 2024)
Although research on lexicalization has been extensively documented, little is known about over- and under-lexicalization in translation. "Laut Bercerita" and its translation contain mostly violent physical expressions, leading to either excessive or deficient lexical representation compared to the source text. This research aims to analyze over- and under-lexicalization in expressions of physical violence in the novel "Laut Bercerita" and its translation "The Sea Speaks His Name". The research method used is comparative descriptive, which combines comparing the meanings of the source text and target text. Data were collected using note-taking techniques. In the analysis stage, the data were first segmented or classified based on categories of physical violence. Subsequently, the data were analyzed by adopting a lexical variation of Fowler’s theory. The results of the study showed that over-lexicalization occurred in the form of physical violence such as (1) kicking, (2) torturing, (3) electric shocking, (4) slapping, (5) punching, and (6) stepping on, accounting for 47%. Meanwhile, under-lexicalization occurred in the form of physical violence such as (1) hitting, (2) kicking, (3) torturing, (4) electric shocking, (5) handcuffing, (6) punching, and (7) stepping on, accounting for 57%. Under-lexicalization occurs when there is a reduction of lexical items and simplification of meaning concepts, while over-lexicalization occurs with the addition of lexical items and complex meanings. Over-lexicalization and under-lexicalization imply that the translation may not meet standard translation norms through lexicon choices but still maintains equivalence.